Lima guru agung Jawa: kisah dan ajaran lima sufi agung Jawa, Syekh Siti Jenar, Ki Ageng Pengging, Syekh Malang Sumirang, Syekh Amongraga, R. Ng. Rongga Warsito - Agus Wahyudi (Lingkaran Press, 2016)
et,1/why, c.1